5′ to 3′ Unfolding Directionality of DNA Secondary Structures by Replication Protein A: G-QUADRUPLEXES AND DUPLEXES - Safa, Layal (J Biol Chem, 2016)
The replication protein A (RPA) is a single-stranded DNA-binding protein that plays an essential role in DNA metabolism. RPA is able to unfold G-quadruplex (G4) structures formed by telomeric DNA sequences, a function important for telomere maintenance. To elucidate the mechanism through which RPA unfolds telomeric G4s, we studied its interaction with oligonucleotides that adopt a G4 structure extended with a single-stranded tail on either side of the G4. Binding and unfolding was characterized using several biochemical and biophysical approaches and in the presence of specific G4 ligands, such as telomestatin and 360A. Our data show that RPA can bind on each side of the G4 but it unwinds the G4 only from 5′ toward 3′. We explain the 5′ to 3′ unfolding directionality in terms of the 5′ to 3′ oriented laying out of hRPA subunits along single-stranded DNA. Furthermore, we demonstrate by kinetics experiments that RPA proceeds with the same directionality for duplex unfolding.